Detection of HPV and Human Chromosome Sites by Dual-Color Fluorescence In Situ Hybridization Reveals Recurrent HPV Integration Sites and Heterogeneity in Cervical Cancer - Xiong, Jinfeng; Cheng, Jing; Shen, Hui; Ren, Ci; Wang, Liming; Gao, Chun; Zhu, Tong; Li, Xiaomin; Ding, Wencheng; Zhu, Da; Wang, Hui (Frontiers in Oncology, 2021)
Human papillomavirus (HPV) integration in the human genome is suggested to be an important cause of cervical cancer. With the development of sequencing technologies, an increasing number of integration "hotspots" have been identified. However, this HPV integration information was derived from analysis of whole cervical cancer tissue, and we know very little about the integration in different cancer cell subgroups or individual cancer cells. This study optimized the preparation of probes and provided a dual-color fluorescence in situ hybridization (FISH) method to detect HPV integration sites in paraffin-embedded cervical cancer samples. We used both HPV probes and site-specific probes: 3p14 (FHIT), 8q24 (MYC), 13q22 (KLF5/KLF12), 3q28 (TP63), and 5p15 (TERT). We detected HPV signals in 75 of the 96 cases of cervical cancer; 62 cases showed punctate signals, and 13 cases showed diffuse punctate signals. We identified 3p14 as a high-frequency HPV integration site in 4 cervical cancer cases. HPV integration at 8p14 occurred in 2 cases of cervical cancer. In the same cervical cancer tissue of sample No.1321, two distinct subgroups of cells were observed based on the HPV probe but showed no difference in cell and nucleus morphology. Our study provides a new method to investigate the frequent HPV integration sites in cervical cancer and reports the heterogeneity within cervical cancer from the perspective of HPV integration.